2013
DOI: 10.1007/s00267-013-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Participation in U.S. Farm Bill Conservation Programs

Abstract: Conservation policy in agricultural systems in the United States relies primarily on voluntary action by farmers. Federal conservation programs, including the Environmental Quality Incentives Program, offer incentives, both financial and technical, to farmers in exchange for adoption of conservation practices. Understanding motivations for (as well as barriers to) participation in voluntary programs is important for the design of future policy and effective outreach. While a significant literature has explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 54 publications
0
74
1
Order By: Relevance
“…For the Upper Salt Fork, 90 completed surveys were returned out of 284 surveys sent, minus 13 returned for ineligibility and 1 undeliverable address, yielding a 33.3% response rate. Although limiting in terms of representation, these rates are higher than similar recent studies (e.g., 21.9%, as reported by Reimer and Prokopy [2013]). Comparisons were made with agricultural census statistics for the two counties and the state of Illinois (Table 1).…”
Section: Farm Operator and Landowner Interview Methodscontrasting
confidence: 52%
See 1 more Smart Citation
“…For the Upper Salt Fork, 90 completed surveys were returned out of 284 surveys sent, minus 13 returned for ineligibility and 1 undeliverable address, yielding a 33.3% response rate. Although limiting in terms of representation, these rates are higher than similar recent studies (e.g., 21.9%, as reported by Reimer and Prokopy [2013]). Comparisons were made with agricultural census statistics for the two counties and the state of Illinois (Table 1).…”
Section: Farm Operator and Landowner Interview Methodscontrasting
confidence: 52%
“…The lack of consistent findings across projects, time, or geographic study areas indicates that context likely matters when trying to understand farmers' motivations. Additionally, recent literature on agricultural conservation has focused largely on participation in conservation programs and combines inquiry on soil erosion with nutrient runoff and water quality (Arbuckle, 2013;Reimer and Prokopy, 2013), making it difficult to parse perspectives on water quality and nutrients from other more traditional farm conservation issues. Rural Iowa farmers and residents saw the benefits of conservation for water quality but rarely prioritized them or saw them as compatible with farming objectives or constraints (Atwell et al, 2009a(Atwell et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth highlighting the social cobenefits that accrue to participating farms and regional communities (Greiner and Stanley, 2013). However, as experiences elsewhere have shown, they need to be part of a policy bundle to ensure participation of farmers with different property situations, cost structures, and needs and motivations (Reimer and Prokopy, 2014). In particular, information and extension efforts should focus on increasing awareness of biodiversity and grazing impacts, thus changing attitudes relating to biodiversity, increasing acceptance of AES and Note: SE = standard error, ***, **, * denotes significance at 1%, 5%, 10% levels.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of widespread 'cultural' resistance by farmers to participation in AES (Burton et al, 2008;Defrancesco et al, 2008) while research into AES participation across Europe found that conservation orientation was equally as important as financial motivation (Wilson and Hart, 2000). Personal factors include values, attitudes, motivations and perceptions and various social-psychological models and theories have been developed to explore and explain their influence on farmer behaviour (Beedell and Rehman, 2000;Burton, 2004;Greiner and Gregg, 2011;Johansson et al, 2013;Reimer and Prokopy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the Yahara Watershed, funding and programmatic constraints affected opportunities for spatial targeting. Reimer and Prokopy (2014) found that the complexity of the USDA incentives system may be a barrier that prevents participation by farmers with scarce time or resources. They suggested outreach efforts to increase awareness of program options, and future policy that balances program flexibility with complexity.…”
Section: Barriers To Spatial Targeting For Water Quality Protectionmentioning
confidence: 98%